Detecting Fraudulent Financial Reporting in Manufacture Sector - Handoko, Bambang Leo; Juandy, Tesare Novan (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of this research is to analyze the influence of Financial Targets, Financial Stability, Auditor Change, and effective monitoring to the detection of financial statements at manufacturing companies in the consumer goods industry sector. This research data uses secondary data from the Indonesia Stock Exchange. The sample is determined by purposive sampling technique and there are 33 companies listed on the stock exchange and 6 companies that do not submit the financial statements in 2015 - 2017 The results of data analysis show that the analysis model produces 12.84% prediction accuracy and there are 1 (one) variables that influence significant and there were 3 (three) significant influential variables namely Financial Target, Financial Stability, Auditor Change to detect fraudulent financial statements.